2011
DOI: 10.1038/ncomms1376
|View full text |Cite
|
Sign up to set email alerts
|

Imaging local electronic corrugations and doped regions in graphene

Abstract: Electronic structure heterogeneities are ubiquitous in two-dimensional graphene and profoundly impact the transport properties of this material. Here we show the mapping of discrete electronic domains within a single graphene sheet using scanning transmission X-ray microscopy in conjunction with ab initio density functional theory calculations. scanning transmission X-ray microscopy imaging provides a wealth of detail regarding the extent to which the unoccupied levels of graphene are modified by corrugation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
144
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(151 citation statements)
references
References 44 publications
7
144
0
Order By: Relevance
“…hybridization state of carbon atoms in the near-surface region of carbon-based materials, such as diamond [45][46][47][48][49] , amorphous carbon 14,29,[50][51][52] , graphene 53,54 , and polymers [55][56][57] . The dependence of the intensity of the detected spectral features on the orientation of the final state orbital with respect to the electric field vector of the incident photon beam 58 also allows the surface molecular orientation of nanomaterials [59][60][61] and adsorbates 62 to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…hybridization state of carbon atoms in the near-surface region of carbon-based materials, such as diamond [45][46][47][48][49] , amorphous carbon 14,29,[50][51][52] , graphene 53,54 , and polymers [55][56][57] . The dependence of the intensity of the detected spectral features on the orientation of the final state orbital with respect to the electric field vector of the incident photon beam 58 also allows the surface molecular orientation of nanomaterials [59][60][61] and adsorbates 62 to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, Ref. [43] and [47] have found that the more edge C atoms are probed in XAS, the higher the intensity of the pre-edge peak. Moreover, Other kinds of structure modulations like charged-specie adsorption may also create such a pre-edge peak [43,48,49].…”
Section: Edge Effectsmentioning
confidence: 99%
“…The reduced dimensionality and the presence of the edge atoms can strongly modify the electronic and transport properties of graphene. The local electronic structure at the edge of a graphene has been measured by X-ray absorption microscopy [43] and EELS [44,45]. Here we study XANES of a zigzag-type edge terminated by hydrogen, and focus on several particular kinds of carbon atoms which are colored pink and labelled by numbers as shown in Fig.…”
Section: Edge Effectsmentioning
confidence: 99%
“…For carbon K-edge NEXAFS spectroscopy, in particular, the resolvable energy difference between the resonant X-ray excitations of a core-level (1s) electron to unoccupied molecular orbitals (either π* or σ*) allows the identification of the bonding configuration and hybridization state of carbon atoms in the near-surface region for many materials, including diamond 6,13,21,22,24,25,[33][34][35][36][37][38] , diamond-like carbon [39][40][41][42][43][44][45][46] , graphene 26,47,48 , and polymers [27][28][29][30][31][32] , as well as the determination of the surface molecular orientation of nanomaterials 18,19,49,50 and adsorbates [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%